Дослідження гібрідної сонячної панелі на основі циліндричних когенераційних фотомодулів - Галько, Сергій Віталійович; Галько, Сергей Витальевич; Halko, Serhii; Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Samoichuk, Kyrylo (ТДАТУ, 2020)
UK: У статті виконаний аналіз відомих закордонних автономних зарядних станцій на основі плоских сонячних фотоелектричних панелей для зарядки акумуляторних батарей електромобілів. Запропоновано замість традиційних панелей використовувати гібридні сонячні фотоелектричні панелі на основі циліндричних когенераційних фотоелектричних модулів. Розроблено експериментальну установку для дослідження електрофізичних характеристик гібридної сонячної панелі. Отримано вольт-амперні характеристики і характеристики потужності панелі, що розробляється. Виконано порівняльний аналіз розробленої панелі з закордонним аналогом традиційної конструкції і визначена її енергетична ефективність, яка краща на 12,1% від аналогу. RU: В статье выполнен анализ известных зарубежных автономных зарядных станций на основе плоских солнечных фотоэлектрических панелей для зарядки аккумуляторных батарей электромобилей. Предложено вместо традиционных панелей использовать гибридные солнечные фотоэлектрические панели на основе цилиндрических когенерационных фотоэлектрических модулей. Разработана экспериментальная установка для исследования электрофизических характеристик гибридной солнечной панели. Получены вольт-амперные характеристики и характеристики мощности разрабатываемой панели. Выполненный сравнительный анализ разработанной панели с зарубежным аналогом традиционной конструкции и определена ее энергетическая эффективность, которая лучше на 12,1% от аналога. EN: The analysis of the well-known foreign autonomous charging stations, where the use of renewable energy sources based on flat solar photovoltaic panels for charging of electric vehicle batteries is applied, was made in the article. This industry is considered to be one of the most important and promising areas for the development of solar energy in order to save non-renewable energy sources. The refore, instead of traditional flat panels, it was proposed to use hybrid solar photovoltaic panels based on cylindrical cogeneration photovoltaic modules, which make it possible to receive electrical and thermal energy simultaneously, and thereby increase the overall efficiency of the panel. An experimental assembly with stabilization of the temperature of a photoelectric converter has been developed to research the electrical and physical characteristics of a hybrid solar photovoltaic panel. The volt-ampere characteristics and power characteristics of the developed panel were obtained at a temperature of the photoelectric converter of 50 ° C. It was estimated that this coolant temperature is sufficient to provide hot water for administrative buildings of autonomous charging stations. Moreover, it was found that at a maximum density of specific power of solar radiation of 825 W / m2, the developed hybrid solar photovoltaic panel has a maximum power of 381 W with a maximum output voltage of 34 V and an output current of 11 A, and an output specific maximum power of 224 W / m2. Finally, a comparative analysis of the developed hybrid photovoltaic panel with a foreign analogue of a traditional design was carried out. As a result, it was determined that the energy efficiency of the developed photovoltaic panel was by 12.1% better than the energy efficiency of the analogue.
Исследование гибридной солнечной панели на основе цилиндрических когенерационных фотомодулей
Research of the hybrid solar panel based on cylindrical cogenerating photomodules
Keywords: сонячна панель; зарядка акумуляторів; електромобіль; гібридна сонячна панель; когенераційний фотоелектричний модуль; солнечная панель; зарядка аккумуляторов; электромобиль; гибридная солнечная панель; когенерационный фотоэлектрический модуль; solar panel; battery charging; electric vehicle; hybrid solar panel; cogeneration photoelectric module